Preparing for Implementation Within Therapy Services for People With Dementia: Exploring Expectations and Experiences Among Service Providers. (October 2021) - Culph, Jennifer; Clemson, Lindy; Jeon, Yun-Hee; Scanlan, Justin; Laver, Kate
Background: This study examined how occupational therapists, nurses, and their managers within different organizational contexts in the Australian health and aged care system prepare for implementation. The program being implemented was the Care of People with dementia in their Environment (COPE) program, a community reablement program for people with dementia and their carers. Methods: Qualitative data from 29 in-depth interviews were collected from occupational therapists, nurses, and their managers. Recruitment ensured a variety of organizational contexts were included. Thematic analysis was used to capture key themes. Results: Themes include innovation in a time of instability and uncertainty, values that align with the innovation, shifting the day-to-day practice, and confidence in new specialized skills. Conclusion: Organizations need to carefully consider internal and external contexts when planning implementation efforts. Study findings have informed plans for embedding delivery of the program within the health and aged care sector.